2023
DOI: 10.1108/er-10-2022-0491
|View full text |Cite
|
Sign up to set email alerts
|

Coming to work with an illness: the role of high-involvement work systems and individual competence on presenteeism

Abstract: PurposeThis paper aims to examine the effect of high-involvement work systems (HIWSs) on completing work and avoiding distraction as two dimensions of presenteeism. It also investigates competence as a mediator of the effect of HIWS on presenteeism.Design/methodology/approachData were collected from 343 Bangladeshi bank employees using an online survey. The partial least squares-structural equation modelling (PLS-SEM) was employed to assess the abovementioned linkages.FindingsThe findings demonstrate HIWS dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Finally, Islam et al .’s (2024) paper, “Coming to work with an illness: the role of high-involvement work systems and individual competence on presenteeism”, examines the relationship between high involvement work systems (HIWS) and two dimensions of presenteeism by identifying competence as a mediator using the job demands-resources model (JD-R model). Presenteeism is defined as continuing to work despite health concerns.…”
Section: Overview Of Special Issue Papersmentioning
confidence: 99%
“…Finally, Islam et al .’s (2024) paper, “Coming to work with an illness: the role of high-involvement work systems and individual competence on presenteeism”, examines the relationship between high involvement work systems (HIWS) and two dimensions of presenteeism by identifying competence as a mediator using the job demands-resources model (JD-R model). Presenteeism is defined as continuing to work despite health concerns.…”
Section: Overview Of Special Issue Papersmentioning
confidence: 99%
“…Researchers have shown that rewards and recognition are crucial factors influencing affective commitment, work engagement and turnover intention (Islam et al. , 2023a, b). This idea is based on the social exchange theory and a “psychological contract” between employer and employee (Rousseau, 1995; Newman and Sheikh, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to SamGnanakkan (2010), high-involvement HR practices enhanced employee retention, and beneficial actions directed towards employees should obligate employees to reciprocate positively. Such HR practices, where rewards are also recognized (Islam et al ., 2023b), may reinforce the employees’ beliefs that the organization values their contributions and cares about their well-being, which in turn reduces turnover intentions among employees (SamGnanakkan, 2010, p. 50).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation